Neurocognitive correlates of the varied domains of outcomes at 20 year follow-up of first-episode psychosis. (December 2022) - Cuesta, M.J.; Sánchez-Torres, A.M.; Moreno-Izco, L.; García de Jalón, E.; Gil-Berrozpe, G.J.; Zarzuela, A.; Peralta, V.; Ballesteros, A.; Fañanás, L.; Hernández, R.; Janda, L.; Lorente, R.; et al.
Highlights: Most of the dimensions of poor outcome were associated with poorer cognition at the long-term follow-up of FEP. A final diagnosis of schizophrenia or schizoaffective disorder showed the strongest association with cognitive impairment. Impairments in processing speed, verbal and visual memory are associated with poor outcome at the long-term follow-up in FEP. A multi-domain outcome (MDO) approach may allow personalizing the individual long-term outcome in FEP. Caution is needed in generalizing our results from FEP patients admitted more than 20 years ago to current outcomes of FEP. Abstract: Little is known about long-term outcomes of the first episode of psychosis (FEP) other than in the symptomatic domain. We hypothesised that cognitive impairment is associated with poorer multi-domain outcomes at a long-term follow-up of FEP patients. We followed-up 172 FEP patients for a mean of 20.3 years. Ten outcome dimensions were assessed (symptomatic, functional and personal recovery, social disadvantage, physical health, suicide attempts, number of episodes, current drug use, chlorpromazine equivalent doses (CPZ), and schizophrenia/schizoaffective disorder final diagnosis). Cognition was assessed at follow-up. Processing speed and verbal memory deficits showed significant associations with poor outcomes on symptomatic, social functioning, social disadvantage, higher number of episodes, and higher CPZ. Significant associations were found between visual memory impairments were significantly associated with low symptomatic and functional recovery, between attentional deficits and a final diagnosis of schizophrenia/schizoaffective disorder, and between social cognition deficits and poor personal recovery.Lower cognitive global scores were significantly associated with all outcome dimensions except for drug abuse and physical status. Using multiple outcome dimensions allowed for the inclusion of the patients' perspective and other commonly neglected outcome measures. Taken together, cognitive impairment in FEP patients is strongly related to poor performance on several outcome dimensions beyond symptomatic remission.